2013
DOI: 10.1111/bjd.12402
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of superficial basal cell carcinoma (sBCC) predicts imiquimod efficacy: a proposal for a thickness-based definition of sBCC

Abstract: We recommend the use of tumour thickness to define the superficial pattern in pathology reports for BCC as this can help to determine treatment response of sBCC to imiquimod.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 33 publications
1
38
0
2
Order By: Relevance
“…We found no evidence that these histologic parameters have to be taken into 13 also recommended that adnexal extension should be measured in pathology reports, but no statistical analyses were reported to support this finding. Based on our analyses we found no evidence that adnexal extension is a determinant of noninvasive treatment failure in sBCC.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…We found no evidence that these histologic parameters have to be taken into 13 also recommended that adnexal extension should be measured in pathology reports, but no statistical analyses were reported to support this finding. Based on our analyses we found no evidence that adnexal extension is a determinant of noninvasive treatment failure in sBCC.…”
Section: Discussionmentioning
confidence: 58%
“…The maximum tumor thickness of sBCC in the current study was 1.0 mm and therefore the data do not allow conclusions about tumors thicker than 1.0 mm. However, previous findings of McKay et al 13 indicate that thickness of the majority of sBCC does not exceed 1.0 mm.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This distinction is important, as classification of BCC as superficial indicates the patient is a candidate for topical therapy. McKay and co‐workers found BCC thickness of ≤0.4 mm was associated with lack of recurrence after topical imiquimod therapy . One of this study's authors (GRF) found it helpful to apply this threshold in practice using known objective field diameters.…”
Section: Discussionmentioning
confidence: 90%
“…The nodular BCC (nBCC) is the most common histopathological subtype, but an increase in the proportion of superficial BCC (sBCC) and infiltrating BCC (iBCC) has been reported . Within recent years, several non‐surgical treatments have been established for treatment of BCC . The histopathological subtype of BCC is, however, correlated with treatment outcome and recommended treatment options therefore differ.…”
Section: Introductionmentioning
confidence: 99%